2006
DOI: 10.1021/jm0607810
|View full text |Cite
|
Sign up to set email alerts
|

Configurationally Restricted Bismacrocyclic CXCR4 Receptor Antagonists

Abstract: A zinc(II) containing configurationally restricted analogue of bismacrocyclic cyclam-type CXCR4 chemokine receptor antagonists has been synthesized and shown to adopt only one configuration in solution. The single crystal X-ray structure reveals favorable binding to acetate via a bidentate chelation that can be related to the proposed interaction with aspartate on the receptor protein surface. The zinc(II) complex is highly active against HIV infection in vitro. AMD3100 (the octa HCl salt of 1-1′-[1,4-phenylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
102
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 23 publications
3
102
0
Order By: Relevance
“…[14,36] However, herein we focus on novel nonpeptidic low-molecular-weight CXCR4 antagonists. To date, AMD3100 (1), [20,22] Dpa-Zn complex (2), [37] KRH-1636, [27] and other compounds [31][32][33][34][35] have been developed in this and other laboratories as low-molecularweight nonpeptidic CXCR4 antagonists. The present study reports structure-activity relationship studies based on the combination of common structural motifs, such as xylene scaffolds and cationic moieties that are present in the aforementioned compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[14,36] However, herein we focus on novel nonpeptidic low-molecular-weight CXCR4 antagonists. To date, AMD3100 (1), [20,22] Dpa-Zn complex (2), [37] KRH-1636, [27] and other compounds [31][32][33][34][35] have been developed in this and other laboratories as low-molecularweight nonpeptidic CXCR4 antagonists. The present study reports structure-activity relationship studies based on the combination of common structural motifs, such as xylene scaffolds and cationic moieties that are present in the aforementioned compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have previously prepared and structurally characterized several macrocyclic zinc(II) complexes in order to elucidate the selective recognition of macrocyclic zinc(II) complexes by carboxylate ligands [8][9][10]. Nevertheless, only a handful of structurally characterized examples of such complexes are known at present [7][8][9][10][11][12]. As an extension of our investigations on expanding the examples of carboxylato zinc(II) macrocycles, we investigated the reactions of Zn(L)(NO 3 ) 2 (1) and sodium fumarate.…”
Section: Introductionmentioning
confidence: 99%
“…Within the past decade, these macrocycles have become important structural moieties for a variety of diagnostic and therapeutic pharmaceutical agents (21). Our group has been actively involved in the synthesis of these macrocyclic polyamines and their metal complexes and demonstrated their activities against HIV through CXCR4 inhibition (22)(23)(24)(25)(26)(27). We have recently employed the metal coordination approach to prepare a series of metal complexes using cross-bridged and side-bridged tetraazamacrocyclic ligands and have shown that both the ligands and their metal complexes are effective antimalarial agents (22,28).…”
mentioning
confidence: 99%
“…1) for their activities against S. mansoni in vitro and in vivo and present here our findings on their antischistosomal activity. Seven of these 26 compounds (compounds 8, 9, 15 to 17, 20, and 21) are newly described in this report, and for the other compounds, either their antiviral or antimalarial activities have been described previously or they have been submitted elsewhere for synthetic method development and/or to report their antiviral or antimalarial activities (21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%